The enablers and barriers to continue breast milk feeding in women returning to work. (7th January 2016) - Sulaiman, Zaharah; Liamputtong, Pranee; Amir, Lisa H.
Abstract: Aim: To describe the enablers and barriers working women experience in continuing breast milk feeding after they return to work postpartum in urban Malaysia. Background: In Malaysia, urban working women have low rates of breastfeeding and struggle to achieve the recommended 6 months exclusive breastfeeding. Design: A qualitative enquiry based on a phenomenological framework and multiple methods were used to explore women's experiences in depth. Methods: Multiple qualitative methods using face‐to‐face interview and participant diary were used. Data collection took place in urban suburbs around Penang and Klang Valley, Malaysia from March–September 2011. Participants were 40 employed women with infants less than 24 months. Findings: Only 11 of the participants worked from home. Based on the women's experiences, we categorized them into three groups: 'Passionate' women with a strong determination and exclusively breastfed for 6 months, 'Ambivalent' women who initiated breastfeeding, but were unable to sustain exclusive breastfeeding after returning to work and 'Equivalent' women who introduced infant formula prior to returning to work. Conclusion: Passion and to a lesser extent intention, influenced women's choice. Women's characteristics played a greater role in their infant feeding outcomes than their work environment.